Marketing Authorisation Based on Incomplete Clinical Data: International Experience and Prospects - D. V. Goryachev; N. E. Uvarova; G. V. Shukshina (Регуляторные исследования и экспертиза лекарственных средств)
No new drug can be used in clinical practice without marketing authorisation. Acquisition of the necessary amount of clinical data may take several years, which is especially critical for pernicious diseases for which no alternative therapy is available. Lack of treatment options creates conditions in which early introduction of efficacious therapy into clinical practice is becoming crucial. This need resulted in the development of new regulatory approaches aimed at accelerated approval of drugs both by reducing the time frame and by fulfilling post-authorisation requirements. The aim of the study was to review regulatory approaches to the accelerated authorisation procedure based on incomplete clinical data, and analyse their potential use in the Russian Federation. The paper presents an overview of authorisation pathways based on incomplete clinical data, which are used by different regulatory authorities, as well as regulatory approaches used in the Eurasian Economic Union (EAEU) and as part of the Russian national authorisation procedure. It was demonstrated that the approaches used by the US, European, and Japanese regulatory authorities, despite some differences, share a common objective of accelerated approval of drugs that fill an unmet medical need. The EAEU also has a conditional approval procedure, but the proposed criteria do not make it possible to use this approach in a real clinical situation of an unmet medical need. A similar national procedure would make it possible to reach a compromise between the needs of the healthcare system and the sound basis for informed decisions of the regulatory authority. Accelerated introduction of novel drugs that address unmet medical needs would set the national regulation in the area of drug circulation on the right track.